2017
DOI: 10.1136/bmjopen-2016-015645
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-utility and budget impact analyses of the use of NEPA for chemotherapy-induced nausea and vomiting prophylaxis in Italy

Abstract: ObjectiveTo evaluate the efficiency of resources allocation and sustainability of the use of netupitant+palonosetron (NEPA) for chemotherapy-induced nausea and vomiting (CINV) prophylaxis assuming the Italian National Health Service (NHS) perspective. A published Markov model was adapted to assess the incremental cost-utility ratio of NEPA compared with aprepitant (APR) + palonosetron (PALO), fosaprepitant (fAPR) + PALO, APR + ondansetron (ONDA), fAPR + ONDA in patients receiving a highly emetogenic chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…Restelli et al evaluated the incremental cost-utility from the Italian healthcare perspective of NEPA versus APR plus PALO, fosaprepitant (fAPR) plus PALO, APR plus ondansetron (ONDA), and fAPR plus ONDA in patients receiving HEC. Compared to all four comparator regimens, NEPA resulted in decreased incremental medical cost (€30-€71) and increased incremental QALDs (0.08-0.26) in HEC patients [32]. Similarly, from a British healthcare perspective, NEPA was the dominant strategy in HEC patients, resulting in a reduction of costs and a gain of QALDs versus APR + PALO [20].…”
Section: Discussionmentioning
confidence: 92%
“…Restelli et al evaluated the incremental cost-utility from the Italian healthcare perspective of NEPA versus APR plus PALO, fosaprepitant (fAPR) plus PALO, APR plus ondansetron (ONDA), and fAPR plus ONDA in patients receiving HEC. Compared to all four comparator regimens, NEPA resulted in decreased incremental medical cost (€30-€71) and increased incremental QALDs (0.08-0.26) in HEC patients [32]. Similarly, from a British healthcare perspective, NEPA was the dominant strategy in HEC patients, resulting in a reduction of costs and a gain of QALDs versus APR + PALO [20].…”
Section: Discussionmentioning
confidence: 92%
“…Restelli et al reported the cost-effectiveness of NEPA, comparing the combination with NK1-RA (APR or fosaprepitant) and 5-HT3RA (PALO or ondansetron) in patients receiving highly or moderately emetogenic chemotherapy using a Markov model in the Italian medical care system. The results showed that NEPA was more effective and less expensive [28]. The present study compared a triplet regimen of APR, DEX, and PALO against a control of APR, DEX, and GRA in the Japanese medical care system.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25]27,29,31,32,34,35 The efficacy results were analyzed using intention-to-treat approach in 2 RCTs 28,31 and per-protocol analysis or not was reported in the other 10 studies. [22][23][24][25][26][27]29,30,[32][33][34][35] Of the 5 included economic studies, 4 were cost-utility analysis 36,37,39,40 and 1 was a costeffectiveness analysis. 38 The cost-utility analysis by Botteman et al (2020) 36 was conducted using the efficacy data from a phase III noninferior RCT by Zhang et al (2018) 29 to determine the cost-effectiveness of NEPA relative to the granisetron-aprepitant regimen for HEC.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed characteristics of the included SR 21 (Table 2), primary clinical studies (RCTs) [22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Table 3), economic studies [36][37][38][39][40] (Table 4), and guidelines [41][42][43][44][45][46][47] (Table 5) are provided in Appendix 2.…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%